#Godwin. A discursive analysis and typology of strategic references to the thirties and the Second World War in Flemish MPs' tweets. (28th February 2021) - Willaert, Tom; Goyvaerts, Jana
Abstract: In the wake of a series of late-2019 identitarian conflicts, public discourse in the Belgian region of Flanders was marked by references to the 1930s and 1940s as well as debates about the political appropriateness and significance of such historical allusions. Moving beyond a description of how historical references are condensed in digital political communication, the present article investigates a corpus of tweets sent from accounts of Flemish MPs in order to open up interdisciplinary perspectives on, among others, the dynamics of implicit and explicit accusations of fascism, and the complex, contested fields of speech in which the 1930s and 1940s are evoked on social media. It is thereby argued that (1) on Twitter, terminology associated with the 1930s and 1940s blurs boundaries between present and past, (2) that this conceptual flexibility allows these terms to be deployed in support of a range of political strategies, and (3) that these strategies share prominent accusatory aspects. The paper thus makes an evidence-based contribution to our understanding of how the memory and imagery of the 1930s and the Second World War strategically figure in digital political communication. These findings on online conflict and debate dynamics are supplemented with a methodological reflection on the gains of adopting a localized approach to the analysis of social media texts.